Third International Reindeer/ Caribou Symposium, Saariselkä, Finland, 1982 - Skjenneberg, Sven (Rangifer, 1982)
The third international reindeer/caribou symposium was arranged in Saariselkä, Finland, 23-26 August 1982 under the leadership of Dr. Erkki Pulliainen. 125 participants presented 70 lectures and posters. Proceedings will be published in Acta Zoologica Fennica, Volume VII. NOR contributed much to the conference in giving travelling grants to 35 participants from Finland, Norway and Sweden.